2021
DOI: 10.18388/abp.2020_5442
|View full text |Cite
|
Sign up to set email alerts
|

C-type natriuretic peptide stimulates function of the murine Sertoli cells via activation of the NPR-B/cGMP/PKG signaling pathway

Abstract: C-type natriuretic peptide (CNP) is an important regulator of the male reproductive process. Our previous investigations showed that CNP can significantly stimulate the mRNA expression of androgen-binding protein (Abp) and transferrin (Trf) in the rat Sertoli cells, but the pathways responsible for this process remain to be elucidated. We predict that CNP binds the natriuretic peptide receptor B (NPR-B) to regulate expression of ABP and TRF through the intracellular cyclic guanosine monophosphate (cGMP) pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Based on PCR analyses at different times of cooling intervals, the findings of the current study showed that the expression of the hNPR-B gene was elevated significantly in CNP samples in comparison with controls. Our findings are in agreement with those demonstrated by other researchers ( Ueda et al ., 2020 ; Yu et al ., 2021 ; Nakagawa and Nishikimi, 2022 ). NPR-B is a guanylate cyclase-linked receptor that appears to be activated CNP ( Pagel-Langenickel et al ., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on PCR analyses at different times of cooling intervals, the findings of the current study showed that the expression of the hNPR-B gene was elevated significantly in CNP samples in comparison with controls. Our findings are in agreement with those demonstrated by other researchers ( Ueda et al ., 2020 ; Yu et al ., 2021 ; Nakagawa and Nishikimi, 2022 ). NPR-B is a guanylate cyclase-linked receptor that appears to be activated CNP ( Pagel-Langenickel et al ., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the natriuretic peptide (NP) family, such as atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP) and C-type natriuretic peptide (CNP), serve important physiological functions in maintaining cardiovascular homeostasis ( 1 , 2 ). ANP and BNP are primarily synthesized in the heart tissues and circulate in blood, while CNP is mainly produced by vascular endothelial cells and may mediate physiological effects, such as cardiomyocyte contractility, reproduction, cell proliferation ( 2 , 3 ). These peptides exert their effects by binding to NP receptors (NPRs) 1, 2 and 3.…”
Section: Introductionmentioning
confidence: 99%
“…These peptides exert their effects by binding to NP receptors (NPRs) 1, 2 and 3. NPR1, which binds to ANP and BNP, and NPR-B, which is selective for CNP, ( 2 , 3 ) are composed of an extracellular ligand-binding, a transmembrane, an intracellular kinase homology and a C-terminal guanylate cyclase domain ( 4 ). In addition, NP-scavenging receptor (also known as NPR-C) lacks guanylate cyclase activity and mediates NP degradation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%